Ecosystem indices to support global biodiversity conservation. Issue 1 (11th November 2019) - Rowland, Jessica A.; Bland, Lucie M.; Keith, David A.; Juffe‐Bignoli, Diego; Burgman, Mark A.; Etter, Andres; Ferrer‐Paris, José Rafael; Miller, Rebecca M.; Skowno, Andrew L.; Nicholson, Emily
Abstract: Governments have committed to global targets to slow biodiversity loss and sustain ecosystem services. Biodiversity state indicators that measure progress toward these targets mostly focus on species, while indicators synthesizing ecosystem change are largely lacking. We fill this gap with three indices quantifying past and projected changes in ecosystems using data from the International Union for Conservation of Nature (IUCN) Red List of Ecosystems. Our indices quantify changes in risk of ecosystem collapse, ecosystem area and ecological processes, and capture variation in underlying patterns among ecosystems. We apply the indices to three case studies of regional and national assessments (American/Caribbean forests, terrestrial ecosystems of Colombia, and terrestrial ecosystems of South Africa) to illustrate the indices' complementarity and versatility in revealing patterns of interest for users across sectors. Our indices have the potential to fill the recognized need for ecosystem indicators to inform conservation targets, guide policy, and prioritize management actions.